Penguatan Kapasitas Perangkat Desa Bajak II Dalam Pelayanan Publik Era Digital Governance - Rahayu, Desita; Pratama, Sances Harry; Safitri, Salma; Ferta, Oty; Ecclesia, Clara (Jurnal Kewirausahaan dan Bisnis, 2021)
Times are advancing, demands are increasing, Village officials as the frontline as the lowest implementers of development really need to increase human resources in order to be able to adapt and be able to keep up with the times so that public services at the Village level in the digital era are better and more improved. In this case, there are two challenges to public services in Bajak II Village, namely infrastructure challenges, namely digital infrastructure that can support public services, including the availability of an adequate internet network, a Village information menu that is easy to access. The next challenge is human resources, namely the literacy skills of residents in utilizing social media, digital media to access various information and public services. In the process of increasing human resource capacity carried out by the Temon Village government, although there are many obstacles, many efforts have been made to increase the human resource capacity of the Bajak Village Apparatus. Concrete steps taken by the Bajak Village government are participating in and organizing various trainings and technical guidance in accordance with applicable laws and regulations, organizing the improvement of MSMEs, creating a Village website. In order to increase the capacity of village officials in public services, special attention needs to be paid, because it has become a demand with the rotation of the development of an increasingly advanced era, to be able to improve public services in the digital era, it is very necessary to increase human resources and other support resources, such as tools and internet networks to access all information on social media.